2014
DOI: 10.1289/ehp.1307289
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to Criteria Air Pollutants and Congenital Heart Defects in Offspring: Results from the National Birth Defects Prevention Study

Abstract: Background: Epidemiologic literature suggests that exposure to air pollutants is associated with fetal development.Objectives: We investigated maternal exposures to air pollutants during weeks 2–8 of pregnancy and their associations with congenital heart defects.Methods: Mothers from the National Birth Defects Prevention Study, a nine-state case–control study, were assigned 1-week and 7-week averages of daily maximum concentrations of carbon monoxide, nitrogen dioxide, ozone, and sulfur dioxide and 24-hr measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
115
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(125 citation statements)
references
References 32 publications
10
115
0
Order By: Relevance
“…Several studies have examined the association between maternal exposure to ambient air pollution and congenital heart defects, orofacial clefts, and spina bifida (Agay-Shay et al, 2013; Dadvand et al, 2011aDadvand et al, , 2011bDolk et al, 2010;Gilboa et al, 2005;Hansen et al, 2009;Hwang and Jaakkola, 2008;Lupo et al, 2011;Marshall et al, 2010;Padula et al, 2013a;Padula et al, 2013bPadula et al, , 2013cRamakrishnan et al, 2013;Rankin et al, 2009;Ritz et al, 2002;Schembari et al, 2014;Stingone et al, 2014;Strickland et al, 2009;Vinikoor-Imler et al, 2013). However, benzene and (until recently) PM 2.5 have been understudied pollutants in fetal development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the association between maternal exposure to ambient air pollution and congenital heart defects, orofacial clefts, and spina bifida (Agay-Shay et al, 2013; Dadvand et al, 2011aDadvand et al, , 2011bDolk et al, 2010;Gilboa et al, 2005;Hansen et al, 2009;Hwang and Jaakkola, 2008;Lupo et al, 2011;Marshall et al, 2010;Padula et al, 2013a;Padula et al, 2013bPadula et al, , 2013cRamakrishnan et al, 2013;Rankin et al, 2009;Ritz et al, 2002;Schembari et al, 2014;Stingone et al, 2014;Strickland et al, 2009;Vinikoor-Imler et al, 2013). However, benzene and (until recently) PM 2.5 have been understudied pollutants in fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure has been reported to impact fetal growth (Le et al, 2012;Rich et al, 2009), birth weight (Morello-Frosch et al, 2010;Wilhelm et al, 2012), preterm birth (Chang et al, 2012;Rudra et al, 2011), as well as pregnancy conditions such as preeclampsia Wu et al, 2009;Wu et al, 2011). Several studies have also examined the association between exposure to air pollution and select birth defects (Dadvand et al, 2011a(Dadvand et al, , 2011bDolk et al, 2010;Gilboa et al, 2005;Hansen et al, 2009;Hwang and Jaakkola, 2008;Rankin et al, 2009;Ritz et al, 2002;Stingone et al, 2014;Strickland et al, 2009); however, only until recently have studies included PM 2.5 and benzene as pollutants of interest (Agay-Shay et al, 2013;Lupo et al, 2011;Marshall et al, 2010;Padula et al, 2013aPadula et al, , 2013bPadula et al, , 2013cRamakrishnan et al, 2013;Schembari et al, 2014;Vinikoor-Imler et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a number of studies have shown no correlation between PM10 and fetal cardiovascular malformations [17]. An inverse correlation between PM10 and abdominal diaphragmatic defects has also been reported [18] between fine particles (PM2,5 with aerodynamic diameter ≤ 2,5 μm) and vaginal diaphragmatic defects [13,19] and isolated arterial patency [15]. This work studies the congenital malformations, deformations and chromosomal abnormalities related to the gender and age of occurrence in Cyprus and their relation to atmospheric pollution.…”
Section: Introductionmentioning
confidence: 92%
“…These studies may also be subject to confounding from the potential correlation of high ascertainment of birth defects in urban centers and high pollution measurements (Armstrong et al, 2007). Stingone et al (2014) have made a recent contribution to this literature with NBDPS data, with maternal address during early pregnancy linked to data from the nearest air pollution monitor. As usual, multiple testing across 6 criteria air pollutants, and 17 CHD types, make for complex interpretation that requires looking for patterns, particularly doseresponse trends, rather than individually significant results, and correlations between pollutants must also be taken into account.…”
mentioning
confidence: 99%
“…As usual, multiple testing across 6 criteria air pollutants, and 17 CHD types, make for complex interpretation that requires looking for patterns, particularly doseresponse trends, rather than individually significant results, and correlations between pollutants must also be taken into account. Examination by week of pregnancy showed how sensitive the results can be to the specification of the critical exposure window (Stingone et al, 2014). The case-control study design has the advantage in environmental pollution studies of providing early pregnancy residence (the availability of which is a great strength of NBDPS), and rich data on confounding variables.…”
mentioning
confidence: 99%